Draft Annual Plan (2008-2009) and 11th Five Year Plan (2007-12) Part-II (Write-Up) Government of Tripura - Planning Commission (Planning Commission, 2007)
The economy of Tripura is primarily agrarian. Agriculture is the state's dominant sector with a contribution of nearly 30 % to the Net State Domestic Product (NSDP). According to 2001 census, about 52 % of total main workers are engaged in agriculture in Tripura (All India 58%) of which, cultivators are 28% (All India 32%) and agricultural labourers are 24% (All India 26 %). Small and marginal farmers constitute 90% of the total farmers in the state (All India 78%). The net sown area is only about 27% of the state’s geographical area (All India 57%). Availability of cultivable land is one of the main constraints in the state.
Planning (P and C) Department, Government of Tripura
Planning (P and C) Department, Government of Tripura